Can Public Health Spending Mitigate the Impact of CO2 Emissions on Child Mortality in Sub-Saharan Africa SSA? - Ibrahim Iliyasu; Suleman Lawal Gambo; Abubakar Sabitu (Universitas Airlangga, 2025)
Objective: This study aligns with the actualisation of SDGs targets 3.2, 11.6, 13.3 and 17.1 in Sub-Saharan Africa and contributes to the contemporary discourse on health-environment-public policy dynamics. Specifically, it examines the individual and interactive effect of carbon dioxide emission and per capita public health spending on child mortality. Methods: Data on 44 SSA countries over the years 2000-2020 was analysed using a set of Panel estimation techniques (pool OLS, FE and 2-step difference GMM). Findings: The findings suggested that CO2 emissions have significant increasing impact on “infant and under-five mortality rates”; while, higher per capita public health spending decrease the level of infant and under-five mortality rates. The interaction term indicates that per capita public health spending can dampen the adverse impact of C02 emissions on infant and under-five mortality rates. Originality/Value: evidence suggested that increase in per capita public health spending amid rising CO2emissions works to neutralise the adverse impact of CO2 emissions on “infant and under-five mortality rates. Thus, the study contributes to integrating health-environment-public policy literature. Practical/Policy implication: The study provides insight for the imperative of achieving global CO2 emissions reduction target and increasing average per capita public health spending in SSA.